Combates mortais: análise metodológica de pesquisas experimentais sobre jogos digitais e violência - Monteiro, Louise de França (2017)
One of the most popular forms of entertainment these days is video games, made in different formats and with different contents. A social concern lies about the violent content of the games and the effects that could generate in the players. Even after decades of studies in the area it has not yet been possible to obtain consistent results, leading to two perspectives on the effects of the games: they would be beneficial or harmful. The researches have several methodologies and the study of violent behavior has, in fact, ethical obstacles that make it difficult to measure them. Yet, much of the production of this knowledge relies on cognitive or internalist theoretical bases. The objective of this study was: (a) to identify the methodological characteristics of experimental researches in the Psychology research area that studies the relationship between violence and digital games, in the period from 2011 to 2016; and (b) analyze the methodology of the selected researches, based on the theoretical reference of the Behavior Analysis, in order to indicate contributions to study the relationship between digital games and violence. The sources of information were articles published in two databases: Academic Search Premier and Science Direct. A total of 38 papers were selected, which were analyzed according to external validity and internal validity criteria for experimental research, as well as some of the criteria proposed by Baer, Wolf and Risley (1968) for applied research in Behavior Analysis. Results showed that not all criteria applied to these surveys were completely satisfied. The Analytic criterion was adequately considered, the criteria Generalizable, Conceptual, Behavioral and Technological were partially contemplated. The results of the analyzed research, in turn, show a higher percentage of research that did not find any effects, but there were still a significant number of researches that found harmful and even beneficial effects, indicating that the field is still open to research. Future research may consider collecting articles for longer periods of time and other databases as well as applying the criteria more individually for the articles